Pengaruh Work-Life Balance dan Self-Efficacy Terhadap Job Satisfaction Karyawan Dengan Employee Engagement Sebagai Variabel Intervening Pada PT. PLN (Persero) Pusat Manajemen Proyek - Setiono, Bambang; Bahri, Ronny Samsul (Syntax Corporation, 2025)
This study was conducted with the aim of understanding and analyzing whether work-life balance and self-efficacy influence job satisfaction, with employee engagement serving as a mediating variable at PT. PLN (Persero) Pusat Manajemen Proyek. The research was designed using an explanatory approach. The population of this study consisted of 376 individuals, while the sample size was 65 respondents. The data sources included primary data obtained directly through interviews, observation, and questionnaires, as well as secondary data gathered through literature studies from journals, books, and other references. The analysis method employed in this research was Partial Least Squares (PLS) analysis, facilitated by the SmartPLS 4.0 software. The results of the research and data processing indicated the following: Work-life balance has an effect on employee engagement at PT. PLN (Persero) Pusat Manajemen Proyek, 2) Self-efficacy has an effect on employee engagement at PT. PLN (Persero) Pusat Manajemen Proyek, 3) Work-life balance has an effect on job satisfaction at PT. PLN (Persero) Pusat Manajemen Proyek, 4) Self-efficacy has an effect on job satisfaction at PT. PLN (Persero) Pusat Manajemen Proyek, 5) Employee engagement affects job satisfaction at PT. PLN (Persero) Pusat Manajemen Proyek, 6) Work-life balance affects job satisfaction through employee engagement at PT. PLN (Persero) Pusat Manajemen Proyek, 7) Self-efficacy affects job satisfaction through employee engagement at PT. PLN (Persero) Pusat Manajemen Proyek.